The Median Effective Analgesic Concentration of Ropivacaine in Sciatic Nerve Block Guided by Ultrasound After Arthroscopic Anterior Cruciate Ligament Reconstruction: A Double-Blind Up-Down Concentration-Finding Study - Xu, Cheng; Gu, Fei; Wang, Chengyu; Liu, Yang; Chen, Rui; Zhou, Quanhong; Lu, Jie (Frontiers in Medicine, 2022)
Background The median effective analgesic concentration (MEAC; EC50 = effective concentration in 50% patients) of ropivacaine in sciatic nerve block guided by ultrasound (US) required for effective postoperative analgesia following arthroscopic anterior cruciate ligament (ACL) reconstruction has not yet been found. This study aimed to determine the effectiveness of MEAC of 20 ml ropivacaine of postoperative anesthesia for patients after ACL reconstruction. Methods In total, 29 patients who underwent elective arthroscopic ACL reconstruction were enrolled in this study. All the subjects were given 20 ml of 0.2% ropivacaine for femoral nerve block. A concentration of 20 ml ropivacaine administered to the sciatic nerve was measured by applying the up-and-down sequential method (UDM). The starting concentration was 0.2% in the first patient, and the next patient received decremented 0.025% ropivacaine if the prior patient's postoperative visual analog pain score was <4 in the initial 8 h. Otherwise, the participant was given an incremental dose of 0.025% ropivacaine. The EC50 of ropivacaine was determined by using centered isotonic, linear-logarithmic, exponential regressions, and linear regression. The “goodness of fit” was compared among various models by calculating the residual standard errors. Results The concentration of ropivacaine administered ranged from 0.1 to 0.2%. The EC50 [95% confidence interval (CI)] determined by four statistical methods (centered isotonic, exponential regressions, linear-logarithmic, and linear regression) was 0.115, 0.113% (0.108, 0.343%), 0.142% (0.112, 0.347%), and 0.129% (0.103, 0.359%), respectively. Among all models, the residual standard error was the smallest for the exponential regression (0.2243). Conclusion The EC50 of ropivacaine in US-guided sciatic nerve block was 0.113–0.142%, and exponential regression model best matched the data.